A general best-fitting equation for the multimodal soil–water characteristic curve - Zhao, Yan (2023)
The soil–water characteristic curve (SWCC) is one of the most crucial and fundamental soil properties in unsaturated soil mechanics. Many theories and equations have been developed to describe and best fit SWCC with unimodal or bimodal characteristics. In this study, a general best-fitting equation for SWCC with multimodal characteristics (bimodal and trimodal SWCC) is proposed. The parameters in the proposed equation are closely related to the properties of soil and variables in the SWCC. To evaluate the performance of the proposed equation in best-fitting multimodal SWCC that has more than two modalities, a trimodal SWCC soil mixture that consists of sand, kaolin and activated carbon has been prepared and tested in the laboratory in this study. The proposed equation has been evaluated with data from published literature and the newly developed soil mixture of trimodal SWCC. The proposed equation has shown high accuracy for best-fitting bimodal SWCC and trimodal SWCC.